Social movement organizations' agency for sustainable organizing - Etchanchu, Helen (Edward Elgar Publishing, 2021)
This chapter argues that social movement organizations (SMOs) are relevant actors in the sustainability transition. It presents strategies, success factors and challenges of sustainability SMOs, emphasizing their agency in mobilizing collective action to achieve sustainability goals. We discuss different strategies (aimed at collaboration, confrontation, or prefiguration), organizational forms (characterized by different degrees of organizing) and outcomes (at organizational, community and societal levels) of SMOs. We then illustrate our take of the literature on sustainability SMOs using the recent example of Extinction Rebellion that one of us investigated through participant observation. We conclude with a few avenues for future research, including digital and transnational movements, their potential to transform dominant neoliberal narratives, and the role of academic agency for sustainable organizing.